Better Neighbors : Toward a Renewal of Economic Integration in Latin America - Bown, Chad P.; Lederman, Daniel; Pienknagura, Samuel; Robertson, Raymond (Washington, DC: World Bank, 2016)
This book proposes a renewal of 'Open Regionalism' in Latin America and the Caribbean (LAC) aimed at achieving the region's goals of high growth with stability. The LAC region experienced a growth spurt with equity during the first decade of the 21st Century. It is well understood that an unsustainable demand boom fueled by terms-of-trade improvements drove this growth acceleration episode, especially in South America. Unfortunately, terms of trade are no longer fueling growth, and the region’s policymakers are in search of new sources of growth with stability. With the experience of East Asia and the Pacific in mind, many policymakers in LAC are looking to international economic ties as a potential source of stable growth.